Chinese University Students' Perceptions of the Use and Effectiveness of Turnitin in EAP Writing - Qiufang Zheng (Cranmore Publishing, 2021)
Student plagiarism has been prevalent in academic discourse. This paper investigates through a questionnaire and interviews the use and effectiveness of Turnitin, a major plagiarism detection system, in Chinese university students' EAP writing in a Sino-foreign joint institute in Shanghai. The study finds except for its online marking tool GradeMark, Turnitin has been well-received by most students. Two most welcomed features are the similarity report and its convenience in submitting assignments. Besides, most students perceived Turnitin as an effective tool in reflecting and reducing plagiarism in their writing. However, the study also shows although students' general understanding of the Western concept of plagiarism has been greatly improved, some students may still have misconceptions, and lack sufficient knowledge of what constitutes plagiarism, which can be a major factor contributing to the high similarity rate in their writing on Turnitin. Based on these findings, the study puts forward suggestions on how to reduce student plagiarism in EAP writing, in particular pointing out the introduction of Turnitin in EAP writing instruction in EFL contexts may help to cut down plagiarism.